El contexto internacional y el contexto interior de la guerra española en la actuación de la diplomacia vaticana - Marquina, Antonio (UNISCI Discussion Papers, 2006)
The Spanish Civil War was an important trouble for Vatican diplomacy. The situation during the first months in the Republican zone, with everything religious – Catholic being suppressed in almost all the territory under its jurisdiction, persecution which continued once the Popular Front government was established, and the lack of guarantees for freedom of religious practices until shortly before the end of the war, were conditioning factors that prevented a rapprochement between the Vatican and the Popular Front government. General Franco’s government, on the contrary, supported the Catholic Church. This does not mean that some important disagreements existed between the Vatican and Franco’s government. The question of recognition, the execution of Basque priests, the attempts at making the Vatican condemn the alliance of the Basque nationalist Party with the Popular Front government, the mediation attempts, the bombing of the civilian population and Germany and Italy’s support for Franco’s government were points of special friction and preoccupation. This explains why the appointment of Cardinal Pacelli as Pope Pious XII was regarded by Franco’s government with extreme coolness.